Makna Kematian pada Muslim Lanjut Usia - Muzdalipah Muzdalipah; Iredho Fani Reza; Zaharuddin Zaharuddin (Jurnal Psikologi Islam dan Budaya, 2018)
At a later age, the thoughts of death often come around. This research usedphenomenological research design, to explore how elderly people understand the meaning of deathThe subjects in this study are four elderly participantsin the Tresna Werdha Teratai Palembang orphanage. The subject was collected using purposive sampling and data collection techniques used semi-structured interview. The results of this study indicate that the meaning of death in the elderly is an event and a warning that must be felt by every human being, the subject was troubled by the circumstances that will be experienced when sakaratulmaut later and worry died in the circumstances su'ul khotimah. However, all subjects try to avoid the fear and worry, and performing worship such as praying for five times everyday, remembrance of Allah, and avoid prohibition from Allah Swt. Factors influencing the meaning of death are experiential factors and environmental factors.